IMPLEMENTASI LATDAMPING DALAM RANGKA MENGHASILKAN RKS BERBASIS KEBUTUHAN MELALUI MODEL EDS - Nurmaini . (Jurnal Ilmiah Dikdaya, 2017)
Abstract : This school action research is aimed at increasing the ability of School Development Team in designing School Development Program through training in a form of (Pelatihan and Pendampingan or LATDAMPING ) The subjects of this research are School Development Team ( SDT ) of SMA N 5, SMA PGRI 2, SMA Bina Kasih and SMA Unggul Ikabama Kota Jambi.The Data about School Development Program was collected through interview, document, observation and instrument. This research consists of two cycles. The result of sycle 1 states that achievement of SMA N 5 is 75%, SMA PGRI 2 reached 76%, SMA Bina Kasih reached 76% too and SMA Unggul Ikabama got 68%. There increasing percentage of each school  is SMA N 5 50%, SMA PGRI 2 50%, SMA Bina Kasih 58.8% and SMA Unggul Ikabama 60%. In cycle two, the four schools got  high increase. The result of SMA N 5 reached 84%, SMA PGRI 2 reached 88%, SMA Bina Kasih reached 86%, and SMA Unggul Ikabama 78% Based on this result can be concluded that LATDAMPING is significant enough to increase the ability of SDT in designing School Development program.Keywords: Pelatihan, Pendampingan, RKS, EDS